Human herpesvirus 6 is closely related to human cytomegalovirus. - Lawrence, G L (1990)
A sequence of 21,858 base pairs from the genome of human herpesvirus 6 (HHV-6) strain U1102 is presented. The sequence has a mean composition of 41% G + C, and the observed frequency of CpG dinucleotides is close to that predicted from this mononucleotide composition. The sequence contains 17 complete open reading frames (ORFs) and part of another at the 5' end of the sequence. The predicted protein products of two of these ORFs have no recognizable homologs in the genomes of other sequenced human herpesviruses (i.e., Epstein-Barr virus [EBV], human cytomegalovirus [HCMV], herpes simplex virus [HSV], and varicella-zoster virus [VZV]). However, the products of nine other ORFs are clearly homologous to a set of genes that is conserved in all other sequenced herpesviruses, including homologs of the alkaline exonuclease, the phosphotransferase, the spliced ORF, and the major capsid protein genes. Measurements of similarity between these homologous sequences showed that HHV-6 is clearly most closely related to HCMV. The degree of relatedness between HHV-6 and HCMV was commensurate with that observed in comparisons between HSV and VZV or EBV and herpesvirus saimiri and significantly greater than its relatedness to EBV, HSV, or VZV. In addition, the gene for the major capsid protein and its 5' neighbor are reoriented with respect to the spliced ORFs in the genomes of both HHV-6 and HCMV relative to the organization observed in EBV, HSV, and VZV. Three ORFs in HHV-6 have recognizable homologs only in the genome of HCMV. Despite differences in gross composition and size, we conclude that the genomes of HHV-6 and HCMV are closely related.